PENGARUH MODELPROBLEM BASED LEARNING TERHADAP HASIL BELAJAR IPS SISWA KELAS IV SEKOLAH DASAR - Deswita, Putri; Nasrul, Nasrul; Rahmatina, Rahmatina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This research is conducted to reveal the effects of Problem Based Learning (PBL) Model on the students’ learning achievement in Social Science. This quasi-experimental research was conducted by applying The Non-equivalent Pretest-Posttest Control Group Design. The population of the research was 56 students in the 4thgrade of SDN 10 Bandar Buat. The samples were chosen by using Saturation Sampling Technique. The instrument of the research is an objective test. The data obtained were analyzed by using inferential statistic technique. The results found that the average score of the post-test of the control group is 67.63 and the experimental group is 76.3. Key Terms: PBL model; Social Science; Learning Achievement